Цифровий каталог хрестів-енколпіонів колекції В. В. Тарновського - Сита, Л.Ф.; Скороход, В.М.; Жигола, В.С. (Археологія, 2024)
Публікацію присвячено 3D-моделям хрестів-енколпіонів із зібрання Чернігівського історичного музею, а саме хрестам-релікваріям із розкопок і випадкових знахідок на городищі Княжа Гора та його околицях, що входили до колекції В. В. Тарновського. Розглянуто процес фотограмметричної фіксації та представлено результати створення цифрового каталога. Today, preserving Ukraine’s cultural heritage is an integral task for museum organisations and research institutions. Digitising museum collections has become an important and timely task for museum’s employees. The creation of 3D-models of one of the collections of crosses-encolpions of the 10th—13th centuries which is stored in the repository of the Chernihiv Historical Museum named after V. V. Tarnovskyi was no exception. It took place in 2023 with the support of the Deutsches Archäologisches Institut (DAI). The aim of the project was to create a publicly available digital catalogue of the collection, which is posted on the website of the mentioned Museum named after V. V. Tanrnovskyi and on the sketchfaom/horm (fig.1). 53 encolpion crosses were in the archaeological part of the collection of V. V. Tarnovskyi at the end of the 19th century. Today only 21 encolpions from this collection are preserved in the Museum. Almost all reliquary crosses from the collection are dated to the period of Kyivan Rus, and only one item was an import from the Byzantine provinces. Various types of encolpions are represented: crosses with relief images (the most numerous), with blackened images and relief-blackened encolpion crosses. A rare type of reliquary crosses includes an encolpion back leaf with a relief image of John the Baptist with an accompanying inscription. Three-dimensional modeling and corresponding photogrammetric recording is quite widely used to digitise the smallest moving artefacts. Models are used for advanced recording and digital preservation of data, visualisation of research results, additional metrological studies, computer reconstructions, etc. Method of photogrammetric surveying was used during the creation of a digital catalogue of 3D-models of encolpion crosses. The result of the project is the creation of a multimedia visualised digital catalogue of the collection of encolpion crosses in free access on the global network, which presents a moving 3D-model of each arteifact and the main descriptive information. This will ensure the preservation of arteifacts in the digital dimension, their use in the Museum’s inteactive exhibitions, the creation of an accurate material copy of the arteifact, and allow remote analysis of materials by scientists for consultations, familiariszation wit artefacts, scintific analysis and writing of scientific articles.